Adverse Events and Resource Utilization After Spinal and General Anesthesia in Infants Undergoing Pyloromyotomy. Issue 4 (1st July 2016) - Ing, Caleb; Sun, Lena S.; Friend, Alexander F.; Roh, Arthur; Lei, Susan; Andrews, Howard; Li, Guohua; Williams, Robert K.
Abstract : Background and Objectives: Interest in spinal anesthesia (SA) is increasing because of concern about the long-term effects of intravenous (IV) and inhaled anesthetics in young children. This study compared SA versus general anesthesia (GA) in infants undergoing pyloromyotomy. Methods: Between 2000 to 2013, the University of Vermont Medical Center almost exclusively used SA for infant pyloromyotomy surgery, whereas Columbia University Medical Center relied on GA. Outcomes included adverse events (AEs) within 48 hours of surgery, operating room (OR) time, and postoperative length of stay (LOS). Regression was used to evaluate the association between anesthesia technique and outcomes, accounting for demographic and clinical covariates. Results: We studied 218 infants with SA at the University of Vermont Medical Center and 206 infants with GA at Columbia University Medical Center. In the SA group, 96.3% of infants had adequate initial analgesic levels, but 35.8% required supplemental IV or inhaled anesthetic agents. Compared with GA, the risk of AEs in SA (adjusted odds ratio, 0.60; 95% confidence interval [CI], 0.27–1.36) did not significantly differ, but SA was associated with shorter OR times (17.5 minutes faster; 95% CI, 13.5–21.4 minutes) and shorter postoperative LOS (GA is 1.19 times longer; 95% CI, 1.01–1.40). Conclusions: Infants undergoing pyloromyotomy with SA had shorter OR times and postoperative LOS, no significant differences in AE rates, and decreased exposure to IV and inhaled anesthetics, although SA infants often still required supplemental anesthetics. Whether these differences result in any long-term benefit is unclear; further studies are needed to determine the risk of rare AEs, such as aspiration.